Criminal law protection of religious freedom amid contemporary challenges and threats - Marcin Warchoł (Probacja, 2023)
Religious freedom is of fundamental significance among human rights, because it reaches beyond the temporal. It derives from human dignity. The European Court of Human Rights infers from Article 9 of the Convention for the Protection of Human Rights and Fundamental Freedoms (religious freedom) an obligation for states to provide legalprotection to religious communities and their members as well as objects of religious worship. Criminal law instruments for the protection of religious freedom are accordingly permissible. The paper presents 12 European national legislations that contain relevant criminal law regulations. They provide for punishment for violating the order of religious services and rites, objects of religious worship, as well as religious dogma and doctrine. These approaches are compared to Polish provisions in this respect. A comparative legal analysis has revealed that Poland has significantly weaker protection of religious acts, as well as objects and sites of religious devotion, compared to other countries’ legal systems. This lower standard of protection at the legislative level is confirmed in the adjudicatory practice of Polish courts. Crime criteria stipulated in Articles 194 and 195 of Poland’s Criminal Code, such as the “malicious” character of the perpetrator’s behaviour required for punishment for disrupting or “offending religious feelings”, as a condition for being held culpable for insulting an object of religious worship or site designated for the public performance of religious rites, ensure in effect the impunity of the perpetrators of these deeds. Their adjudicatory interpretation tends to grant those manifesting their hostility to religious faith and doctrine the right to disturb religious services and insult objects of religious devotion. As such the citizens’ bill “in defence of Christians”, which envisages the elimination of these criteria and the introduction of a protection of religious freedom, deserves recognition.